Transcriptional profiling of suberoylanilide hydroxamic acid (SAHA) regulated genes in mineralizing dental pulp cells at early and late time points - DUNCAN, HAL; MORAN, GARY; FLEMING, GARRY (My University, 2015)
Dental pulp tissue can be damaged by a range of irritants, however, if the irritation is removed and/or the tooth is adequately restored, pulp regeneration is possible (Mjör and Tronstad, 1974 [1]). At present, dental restorative materials limit healing by impairing mineralization and repair processes and as a result new biologically-based materials are being developed (Ferracane et al., 2010 [2]). Previous studies have highlighted the benefit of epigenetic modification by histone deacetylase inhibitor (HDACi) application to dental pulp cells (DPCs), which induces changes to chromatin architecture, promoting gene expression and cellular-reparative events (Duncan et al., 2013 [3]; Paino et al., 2014 [4]). In this study a genome-wide transcription profiling in epigenetically-modified mineralizing primary DPC cultures was performed, at relatively early and late time-points, to identify differentially regulated transcripts that may provide novel therapeutic targets for use in restorative dentistry. Here we provide detailed methods and analysis on these microarray data which has been deposited in Gene Expression Omnibus (GEO): GSE67175.
PUBLISHED
Keywords: Dental pulp cells; Endodontics; Epigenetics; Histone deacetylase inhibitors; Mineralization; Genes & Society; Molecular Biology